Passos em falso? Os processos de formação do espaço das consultorias em sustentabilidade no Brasil - Botta, Elisa Nogueira Novaes (2013)
The emergence of Sustainable Development and thereafter , of Corporate Sustainability, integrated representative elites of social space that until then were developing independently .Furthermore it showed new ways of conduct in the corporative environment ,favoring the emergence of a new market ,with new actors and services, specialized in orientating the client towards a sustainable conduct . As this idea is institutionalized it starts being adopted among many consulting groups , inaugurating new polarization in this universe, .This doctorate research supported on the new Economic Sociology by Pierre Bourdieui investigated the processes of identity formation and identity construction, such as their relations in this new constituted social space, of Consulting Sustainability in Brazil.